Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/nu10070883
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Levels in the Brain Are Determined by Post-Mortem Interval and Ante-Mortem Vitamin C State but Not Alzheimer’s Disease Status

Abstract: The current study highlighted several changes in measures of oxidative stress and antioxidant status that take place in the mouse brain over the course of 24 h post-mortem. Ascorbic acid (vitamin C) and glutathione both decreased significantly in cortex in as little as 2 h and malondialdehyde levels increased. Further change from baseline was observed up to 24 h, including carbonyl and sulfhydryl formation. The greatest changes were observed in brains that began with low ascorbic acid levels (gulo−/− mice) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…AA metabolites are associated with cellular redox increase of Cox-2 expression, while n-3 PUFA decreases Cox-2 expression (Gravaghi et al, 2011;Mitjavila and Moreno, 2012). Several studies have documented increased oxidative stress in AD brain (Butterfield et al, 1999;Ansari and Scheff, 2010;Bonda et al, 2010;Mosconi et al, 2008;Raukas et al, 2012;Lee et al, 2013;Eckman et al, 2018) typified by increases in reactive oxygen species (ROS). ROS contribute to neurodegeneration and atrophy in neurites (Munnamalai and Suter, 2009).…”
Section: Pufa Inflammation and Oxidative Stressmentioning
confidence: 99%
“…AA metabolites are associated with cellular redox increase of Cox-2 expression, while n-3 PUFA decreases Cox-2 expression (Gravaghi et al, 2011;Mitjavila and Moreno, 2012). Several studies have documented increased oxidative stress in AD brain (Butterfield et al, 1999;Ansari and Scheff, 2010;Bonda et al, 2010;Mosconi et al, 2008;Raukas et al, 2012;Lee et al, 2013;Eckman et al, 2018) typified by increases in reactive oxygen species (ROS). ROS contribute to neurodegeneration and atrophy in neurites (Munnamalai and Suter, 2009).…”
Section: Pufa Inflammation and Oxidative Stressmentioning
confidence: 99%
“…Post-mortem studies have mitigated challenges faced in directly measuring levels of proteins or metabolites from healthy or disease populations like sample tissue collection from live patients. 31 Studying GSH levels in the autopsy brain has provided a baseline for future comparisons with GSH levels found in the same brain regions of patients suffering from neurodegenerative or neuropsychiatric conditions. One of the earliest reports indicated the concentrations of a large group of amino acids along with GSH in different brain regions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Supplementation of the 5XFAD mice under a GULO −/− background with a higher dose of Asc reduces amyloid plaque and ameliorates integrity of the blood–brain barrier and mitochondrial morphology. A later study using these mice also showed that the Asc status, but not Alzheimer’s disease status, was correlated with oxidative stress in the brain [ 89 ].…”
Section: In Vivo Antioxidative Action Of Asc Revealed By Animal Studiesmentioning
confidence: 99%